2009
DOI: 10.1590/s0100-72032009000400003
|View full text |Cite
|
Sign up to set email alerts
|

Geoprocessamento para identificar padrões do perfil de nascimentos na região do Vale do Paraíba

Abstract: this methodology has allowed us to identify spatial clusters for the variables cesarean section and mother's schooling, besides deepening our knowledge on birth profile in the municipalities, presenting good potential on how to direct actions for specific areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
3
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 7 publications
1
10
3
2
Order By: Relevance
“…The results found are alarming when compared to the ones observed as in a national level, 43.89% 10 and 53.7%, 17 as in other Brazilian studies [11][12][13]16 which ranged from 31.1% 12 to 56.3%. 13 However, the proportion of cesarean sections found in this study, corroborates with the proportions identified in 2012 and 2013 in the South Region and were circulated recently by the Ministry of Health, 62% and 62.7%, respectively. 18 Yet, other studies with data from Sinasc in the South Region, also found high percentages of cesarean sections, 60.1% in the South Region in 2011 17 and 60.3% in Santa Catarina State, in 2012.…”
Section: Factors Associated To Maternal and Child's Health In Rio Gracontrasting
confidence: 60%
See 3 more Smart Citations
“…The results found are alarming when compared to the ones observed as in a national level, 43.89% 10 and 53.7%, 17 as in other Brazilian studies [11][12][13]16 which ranged from 31.1% 12 to 56.3%. 13 However, the proportion of cesarean sections found in this study, corroborates with the proportions identified in 2012 and 2013 in the South Region and were circulated recently by the Ministry of Health, 62% and 62.7%, respectively. 18 Yet, other studies with data from Sinasc in the South Region, also found high percentages of cesarean sections, 60.1% in the South Region in 2011 17 and 60.3% in Santa Catarina State, in 2012.…”
Section: Factors Associated To Maternal and Child's Health In Rio Gracontrasting
confidence: 60%
“…22 In relation to the result variables, it was found that in the 19 CRS, most pregnancies had a length of 37 to 42 weeks, however, the proportions of prematurity presented were larger than the estimated 9.2% of prematurity in Brazil, described in a report by the World Health Organization in 2010. 23 Yet, the results for prematurity were high when compared to other studies of the data from Sinasc in Paraná State, which presented 8.1%, 24 in Paraíba Valley in São Paulo with 6.4% 13 and in the South Region, in Santa Catarina State with 10.6% of prematurity in 2012. 19 The highest concentration of prematurity was observed in the CRS in Santa Maria, an medium level region in of the socioeconomic development, 14 this finding seems to be in favor with the description in the study of the data from Sinasc in Santa Catarina, which found a higher prevalence of prematurity among women with a less privileged socioeconomic level.…”
Section: Factors Associated To Maternal and Child's Health In Rio Gramentioning
confidence: 58%
See 2 more Smart Citations
“…In addition, Martins et al 13 conducted an ecological study with spatial focus on healthcare micro-regions in the State of Mato Grosso and they found that fecundity among adolescent women is higher in micro-regions with low indicators of education and socioeconomic development. In this same context, an ecological study 14 aiming to identify the pattern of birth profile in Vale do Paraíba (State of São Paulo, Brazil) showed that the proportion of adolescent mothers is higher in municipalities with less education and less infrastructure.…”
Section: Introductionmentioning
confidence: 99%